Evaluation of the pathogenicity and immunogenicity of seven paracoccidioides brasiliensis isolates in susceptible inbred mice - Singer-Vermes, L. M.; Burger, E. [UNESP]; Franco, M. F. [UNESP]; Moscar Di-Bacchi, M.; Mendes-Giannini, M. J.S.; Calich, V. L.G. (Oxford University Press (OUP), 1989)
In this investigation the pathogenicity and immunogenicity of seven isolates of Paracoccidioides brasiliensis were compared. The pathogenicity of each isolate was determined by 50% lethal dose estimations and histopathology analysed during a 24-week-period. Four basic patterns of virulence could be defined after intraperitoneal infection of susceptible, genetically homogenous, B10.A mice, namely, slightly virulent (isolates Pb 265 and IVIC Pb 267), intermediate (isolates Pb 192, IVIC Pb 9 and Pb SN), virulent (isolate Pb 2052) and highly virulent (isolate Pb 18). The granulomas induced by the individual isolates were similar although the evolution of inflammation and the organs affected varied according to the isolate used. The immunogenicity of each P. brasiliensis isolate was evaluated by measuring IgG titres with an ELISA method. The intermediate and the slightly virulent isolates induced weak antibody production whereas isolates Pb 18 and Pb 2052 induced stronger specific humoral responses. Differences in the kinetics of antibody production elicited by the different fungal isolates were also observed. © 1989 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.